2016
DOI: 10.3920/jcns2014.0007
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder roles for fostering ambidexterity in Sub-Saharan African agricultural netchains for the emergence of multi-stakeholder cooperatives

Abstract: The Sub-Saharan African smallholder agricultural sector faces multiple and usually complex challenges, which can potentially be overcome by collective action. Smallholder farmers and other value chain stakeholders can tackle temporal, structural and contextual challenges by joining multi-level innovation networks to benefit collectively from shared information, knowledge, improved capacities and economies of scale in a process of innovation. Ambidexterity is a capability of innovation networks to balance explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Exploring new markets, expanding existing ones, and improving market access by smallholder farmers may contribute towards sustainable use of the local breeds. In addition, introducing community-based microfinance (i.e., micro-credit, micro-savings, and micro-insurance) co-operatives, which would enable smallholder farmers to lend and/or invest money in groups, gain some bargaining power, and enjoy the benefits of economies of scale, could be of importance for sustainable use of indigenous cattle breeds [80,81].…”
Section: Marketing Strategies For Cattle Productsmentioning
confidence: 99%
“…Exploring new markets, expanding existing ones, and improving market access by smallholder farmers may contribute towards sustainable use of the local breeds. In addition, introducing community-based microfinance (i.e., micro-credit, micro-savings, and micro-insurance) co-operatives, which would enable smallholder farmers to lend and/or invest money in groups, gain some bargaining power, and enjoy the benefits of economies of scale, could be of importance for sustainable use of indigenous cattle breeds [80,81].…”
Section: Marketing Strategies For Cattle Productsmentioning
confidence: 99%
“…While not using the stakeholder theory, VildĂ„sen and Havenvid (2018) and Schneider and Buser (2018), concluded that relations with stakeholders play a crucial role in promoting and developing sustainability. PĂ©rez et al (2016) studying the contribution of various stakeholders in fostering ambidexterity in net chains for tackling challenges faced by smallholder farmers in sub-Saharan African countries, found that the involvement of all local stakeholders in the innovation processes is very significant and emphasize the need to identify all key players in the innovation process. The relevant role of stakeholders in entrepreneurial choices was also emphasized by Reed and Hickey (2016), resulting in a wide variation of knowledge and adoption of innovative practices across cooperative members, due to their ability to control the flow of knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Recall that most of the primary publications focused on the agricultural sector, mainly in an African context. Agriculture is a resource-intensive sector and Africa is regarded as a resource-poor setting, and Agricultural IPs are often formed to pool resources to support smallholder farming (see for example (56,67,91)). This may explain the prominence of Resources and capacity as an engagement theme in the literature.…”
Section: Figure 6: Comparison Of Emphasis On Engagement Practices: Literature and Interviewsmentioning
confidence: 99%